Contrasting Ozark and Great Lakes populations in the endangered Hines emerald dragonfly (Somatochlora hineana) using ecological, genetic, and phylogeographic analyses. Issue 3 (17th January 2020) - Walker, Jane; Mahoney, Meredith; Templeton, Alan R.; McKenzie, Paul; Vogt, Timothy E.; Cashatt, Everett D.; Smentowski, Joseph; Day, Richard; Gillespie, Robert; Henry, Bruce; Wiker, James; Braude, Stanton; et al.
Abstract: The federally endangered species Hine's emerald dragonfly ( Somatochlora hineana ) is found in fens surrounding the Great Lakes region and in a small portion of the Missouri Ozarks. Most previous work has focused on the populations in the Great Lakes region. We present mark/recapture studies and genetic surveys to address the status of the Ozark populations. The densities and genetic diversity tend to be higher in the Ozarks than in the Great Lakes region. A phylogeographic analysis indicates that the Ozarks, with its unglaciated fens, is the likely source for the populations currently inhabiting the formerly glaciated Great Lakes region, and genetic diversity decreases with increasing distance from the Ozarks. This work illustrates the inadequacy of using geography alone to identify a population as marginal and of less conservation concern. We also reanalyzed genetic data on the Great Lakes populations, where several populations have been extirpated over the last several decades. We show that the populations in the Great Lakes region have already lost more than 30% of their genetic diversity over just several decades, and the phylogeographic analysis indicates that increased fragmentation is a possibility in this region due to local extirpations. Ecologically and genetically, the Ozark populations should have a high priority in management plans, and the high rate of loss of genetic diversity and potential fragmentation indicates that continued monitoring and management is needed in the Great Lakes region for this highly endangered dragonfly.